Socialization of e-court implementation based on the jurisdiction in the Karawang district court - Taun; Imanudin Affandi; Rahman (Universitas Ahmad Dahlan, Yogyakarta, 2021)
According to Peraturan Mahkamah Agung Republik Indonesia Nomor 1 Tahun 2019 concerning Administration of Cases and Hearings in Electronic Courts, is the answer to how to conduct the efficiency of the trial by using e-court applications, but the justice seeker community has not effectively done it because of the lack of information and ability to use the e-court application, it is necessary to socialize the application of e-court so that the principle in civil trials which is simple, fast and light costs can be applied properly, furthermore pandemic covid-19 conditions can prevent transmission if the trial is minimized face-to-face by using an e-court application. The method used was to create a banner explaining the flow steps of using an e-court application, then to create infographics and video graphics flow of the use of an e-court application so that the justice seeker community can better understand it, and finally to hold a national webinar to make the scope of e-court application socialization widely known throughout Indonesia. With this devotional activity, partners or Karawang District Court is very helped, because the District Court has to socialize this e-court application so that with this devotional activity the district court becomes helped, the justice seeker community becomes easier in understanding the use of e-court applications, and it is expected that in the future it will be more effective, by still paying attention to the rules of civil procedure law in running the trial online.